General Requirements for Secret Investigative (Search) Actions: Procedural Characteristics - Ya. Yu. Koniushenko (Bulletin of Kharkiv National University of Internal Affairs)
A comprehensive study of the provisions of the Criminal Procedural Code of Ukraine, which regulate the general requirements for secret investigative (search) actions, has been carried out. A comparative analysis of the legislative provisions on the issue has been carried out, which made it possible to distinguish seven groups of general requirements for the implementation of secret investigative (search) actions. The first general requirement of secret investigative (search) actions includes restrictions on their use in criminal proceedings, as they are carried out only in cases where information about the criminal offense and the person who committed it, cannot be obtained in any other way. The second general requirement for conducting secret investigative (search) actions includes restrictions on their use in criminal proceedings, in particular the fact that they are conducted exclusively in criminal proceedings for grave or especially grave offenses. The third general requirement for conducting secret investigative (search) actions is that the legal basis for their implementation is a lawful, reasoned and motivated decision of the investigating judge, issued at the request of the prosecutor or investigator, agreed with the prosecutor. The fourth general requirement for conducting secret investigative (search) actions is that the investigating judge of the appellate court has the right to make the decision to implement them, where the pre-trial investigation agency is within the territorial jurisdiction of that judge. The fifth general requirement includes rules concerning the content of the application for a permit to conduct secret investigative (search) action, the procedure for its consideration by the investigating judge and the content of the decision of the investigating judge. The sixth general requirement for conducting secret investigative (search) actions includes rules that set deadlines for their implementation. The seventh general requirement for conducting secret investigative (search) action includes the rule that the investigator, the interrogator conducting the pre-trial investigation, or, on his behalf or on behalf of the prosecutor, authorized operative units have the right to conduct secret investigative (search) actions.